2009
DOI: 10.1016/j.tem.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Depression as a risk factor for osteoporosis

Abstract: Osteoporosis is a major public health threat. Multiple studies have reported an association between depression and low bone mineral density, but a causal link between these two conditions is disputed. Here we review the endocrine and immune alterations secondary to depression that might affect bone mass. We also discuss the possible role of poor lifestyle in the etiology of osteoporosis in subjects with depression and the potential effect of antidepressants on bone loss. We propose that depression induces bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 62 publications
4
86
1
7
Order By: Relevance
“…Recently, the association between chronic psychological stress and osteoporosis has been the subject of a growing body of research. The published literature, especially recent animal and human studies, showed that chronic psychological stress is a risk factor for developing osteoporosis [11][12][13][14][15]. In the present review, we aim to provide the current understanding of the relationship between chronic psychological stress and osteoporosis.…”
Section: Chronic Psychological Stress As a Risk Factor Of Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the association between chronic psychological stress and osteoporosis has been the subject of a growing body of research. The published literature, especially recent animal and human studies, showed that chronic psychological stress is a risk factor for developing osteoporosis [11][12][13][14][15]. In the present review, we aim to provide the current understanding of the relationship between chronic psychological stress and osteoporosis.…”
Section: Chronic Psychological Stress As a Risk Factor Of Osteoporosismentioning
confidence: 99%
“…Recent studies implicated chronic stress, such as depression in bone loss and osteoporosis, showing there is a link between chronic stress and osteoporosis [11,[31][32][33][34]. Epidemiological studies indicate that depression is an important risk factor for osteoporosis [32][33][34].…”
Section: Relationship Between Chronic Psychological Stress and Osteopmentioning
confidence: 99%
“…One of them, the Nasu-Hakola syndrome, is a genetically heterogeneous disease characterized by a unique combination of systemic bone cysts and dementia with psychotic symptoms similar to schizophrenia. This syndrome is the result of a loss of function mutation in the DAP12 gene located in chromosome 19 [115]. MRI and neuropathological studies of Nasu-Hakola patients have demonstrated the development of calcifications in the basal ganglia and also that frontal lobe syndrome and that dementia begins to develop by age 30.…”
Section: Osteopetrosismentioning
confidence: 99%
“…The activity and level of pro-inflammatory cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), are also increased in depression [21] . Moreover, as potent stimulators of the hypothalamo-pituitary-adrenal (HPA) axis, these inflammatory mediators might contribute to hypercortisolism in depression [22] . The use of antidepressants that have the potential to affect either bone strength or risk of fracture is a possible confounding factor in the association between depression and bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 99%
“…In prospective analyses, current and baseline use of SSRI, but not tricyclic antidepressants (TCAs), have been associated with decreased hip BMD after 5 years of administration [25,26] . Most SSRIs associated with a dose-dependent increase in fracture risk and TCAs, such as amitriptyline and clomipramine, are also associated with the same level of fractures [22] . Animal studies also indicated that serotonin may influence bone mass.…”
Section: Introductionmentioning
confidence: 99%